Purchasing and supply management as a multidisciplinary research field: Unity in diversity?. Issue 5 (December 2019) - Wynstra, Finn; Suurmond, Robert; Nullmeier, Fabian
Abstract: Since the 1960s, research on Purchasing and Supply Management (PSM) has grown substantially, but in recent times various scholars have challenged the actual progress and coherence of the field. In delivering such critiques, the underlying, dominant view of PSM research is that it constitutes an academic discipline. In contrast, we offer an alternative perspective that views PSM as a multi-disciplinary field of research, drawing from Operations Management, Marketing and Strategy & Organization as reference disciplines. Adopting this perspective, we conduct a review of 2522 purchasing and supply management publications in a multi-disciplinary set of 18 high-impact management journals, published in the period 1995–2014. We analyse how PSM research has developed over time; quantitatively and content-wise, in terms of the topics and theories being addressed. We find that across the three reference disciplines and the specialist PSM journals, there is diversity, with distinct features of each journal group in terms of the one or two most popular topics or theories. Still, considering the full base of PSM publications in each journal group, there is considerable overlap. Supplier Relationship Management is a popular topic throughout, and the top-5 of topics for each of the journal groups demonstrates a high degree of overlap, in any given lustrum period. With one exception, TCE is the most popular for all journal groups for all periods and of the 17 different theories identified, only four have been applied by just one journal group. Thus, we conclude that PSM research is characterised by 'unity in diversity': "E Pluribus Unum", and offer recommendations how this multi-disciplinary composition of the field can be leveraged in future research. Highlights: The dominant view of PSM research is that it constitutes a discipline and been maturing only in the last two decades. In contrast, we offer an alternative perspective that views PSM as a multi-disciplinary field of research. This perspective offers a more fine-grained understanding of the development of PSM research.